2000
DOI: 10.1002/1097-4628(20001128)78:9<1579::aid-app10>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Multiple melting behavior of polyphenylene sulfide blends with polyamide 6

Abstract: Although there are many studies on the multiple melting behavior of polyphenylene sulfide (PPS) homopolymer, similar investigations on PPS component in PPS blends with thermoplastics are relatively rare. In the present paper, the multiple melting behavior of PPS blends with polyamide 6 (PA6) have been investigated by differential scanning calorimetry (DSC). The double melting peaks are also observed for PPS in the blends. Although the annealing temperature and time as well as the heating rate of DSC scanning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In addition, some researchers prepared the PPS/polyvinylidene fluoride(PVDF) polymer alloys by melt blending, and the results indicated that the addition of PVDF can accelerate the crystallization of PPS and improve the thermal stability of PPS/PVDF alloys. The multiple melting behaviors of PPS blends with Polyamide 6 were also studied, and the results suggested that PA 6 can accelerate the cold‐crystallization of amorphous PPS. The researchers of also investigated the through‐thickness distribution of liquid crystalline polymer (LCP) in PPS/LCP blends.…”
Section: Blendingmentioning
confidence: 99%
“…In addition, some researchers prepared the PPS/polyvinylidene fluoride(PVDF) polymer alloys by melt blending, and the results indicated that the addition of PVDF can accelerate the crystallization of PPS and improve the thermal stability of PPS/PVDF alloys. The multiple melting behaviors of PPS blends with Polyamide 6 were also studied, and the results suggested that PA 6 can accelerate the cold‐crystallization of amorphous PPS. The researchers of also investigated the through‐thickness distribution of liquid crystalline polymer (LCP) in PPS/LCP blends.…”
Section: Blendingmentioning
confidence: 99%
“…The result suggests that both PTT and mPE components in the blends crystallize individually [21][22][23][24][25]. It is found that the T cIII value of PTT increased by 14.9°C compared with that of A0.…”
Section: Flow Activation Energymentioning
confidence: 99%
“…Nevertheless, the resin has insufficient toughness and is brittle, which limits its application. In recent years, a great effort has been made to improve the above properties, therefore, blending and block copolymerization are necessary [2][3][4][5][6][7][8]. Poly(ether-sulfone) (PES) is an amorphous high-performance engineering plastic with good heat resistance and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%